Dynamic Polarization and Relaxation of 75As Nuclei in Silicon at High Magnetic Field and Low Temperature - J. Järvinen; J. Ahokas; S. Sheludyakov; O. Vainio; D. Zvezdov; L. Lehtonen; L. Vlasenko; S. Vasiliev (SPRINGER WIEN, 2022)
We present the results of experiments on dynamic nuclear polar-
ization and relaxation of 75 As in silicon crystals. Experiments are performed
in strong magnetic fields of 4.6 T and temperatures below 1 K. At these con-
ditions donor electron spins are fully polarized, and the allowed and forbidden
ESR transitions are well resolved. We demonstrate effective nuclear polar-
ization of 75 As nuclei via the Overhauser effect on the time scale of several
hundred seconds. Excitation of the forbidden transitions leads to a polariza-
tion through the solid effect. The relaxation rate of donor nuclei has strong
temperature dependence characteristic of Orbach process.